Librarians and professional status : continuing professional development and academic libraries - Roberts, Norman; Konn, Tania (London : Library Association, 1991)
The first half of the book surveys the ways in which the drive for professional recognition has been found to be linked with training and continuing education issues by other professions. The second half of the book examines the case of academic librarians, and charts their evolving status and its connection with professional development.
"A Clive Bingley Book."
Includes bibliographical references (p. 183-205) and index.
rua 18/09/14
Loans
Keywords: Academic librarians -- Faculty status; Library education (Continuing education)